Muscle Deoxygenation Rates and Reoxygenation Modeling During a Sprint Interval Training Exercise Performed Under Different Hypoxic Conditions - Solsona, Robert; Deriaz, Roméo; Borrani, Fabio; Sanchez, Anthony M. J. (Frontiers in Physiology, 2022)
This study compared the kinetics of muscle deoxygenation and reoxygenation during a sprint interval protocol performed under four modalities: blood flow restriction at 60% of the resting femoral artery occlusive pressure (BFR), gravity-induced BFR (G-BFR), simulated hypoxia (FiO2≈13%, HYP) and normoxia (NOR). Thirteen healthy men performed each session composed five all-out 30-second efforts interspaced with four minutes of passive recovery. Total work during the exercises was 17±3.4, 15.8±2.9, 16.7±3.4, and 18.0±3.0 kJ for BFR, G-BFR, HYP and NOR, respectively. Muscle oxygenation was continuously measured with near-infrared spectroscopy. Tissue saturation index (TSI) was modelled with a linear function at the beginning of the sprint and reoxygenation during recovery with an exponential function. Results showed that both models were adjusted to the TSI (R2=0.98 and 0.95, respectively). Greater deoxygenation rates were observed in NOR compared to BFR (p=0.028). No difference was found between the conditions for the deoxygenation rates relative to sprint total work (p>0.05). Concerning reoxygenation, the amplitude of the exponential was not different among conditions (p>0.05). The time delay of reoxygenation was longer in BFR compared to the other conditions (p<0.05). A longer time constant was found for G-BFR compared to the other conditions (p<0.05), and mean response time was longer for BFR and G-BFR. Finally, sprint performance was correlated with faster deoxygenation and slower reoxygenation. Hence, deoxygenation rates were not different between the conditions when expressed relatively to total sprint work. Furthermore, BFR conditions impair reoxygenation: BFR delays and G-BFR slows down reoxygenation.